Upaya Peningkatan Kemampuan Gerak Dasar Anak Usia Dini Melalui Gerak dan Lagu Berbasis Permainan Digital di Sekolah Minggu GKJ Salatiga Utara - Trivena Dyah Wijayanti; Lika Jipora Hana; Agrecela Prestisya S; Moriend Meilandy Benu; Benedicta Felicia Pramesthi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The purpose of this community service activity is to provide assistance to improve the basic movement abilities of early childhood at GKJ North Salatiga Sunday School through digital game-based motion and song activities and provide training for Sunday school teachers at GKJ North Salatiga regarding the development of digital game media. This method of implementing community service includes assisting in implementing digital game-based play activities and songs to improve the basic movement abilities of early childhood in the 3-6-year-old class of 7 children in Sunday school as well as training in developing simple digital game-based play media for schoolteachers. week of GKJ North Salatiga. Data collection techniques through observation and Likert scale questionnaires were then analyzed using frequency (proportion) analysis techniques. The application of motion and songs based on digital game media can facilitate the improvement of basic locomotor, non-locomotor, and manipulative abilities for early childhood children at GKJ Salatiga Utara Sunday School with the percentage of achievement in the Developing as Expected category reaching 32.9% and Very Well Developing reaching 52.9 %. In the training activities, most of the teachers agreed that the training topics were appropriate and answered the needs of the Sunday school, the delivery of the material was delivered well and was easy to understand, the question-and-answer session ran effectively and increased the teacher's learning interest to apply it in his class.